The Problematic Actuality of Cosmopolitanism - Muñoz Miralles, Albert (Analysis. Journal of Philosophical Research, 2020)
Cosmopolitanism is an old philosophical aspiration, claiming what we share as human beings beyond private belongings. It was expressed as a political project, as a cultural form and as a moral demand. The city offers the elements to make up a cosmopolitan sociability and a democratic way of life, although always threatened by particularist withdrawal. The understanding of cosmopolitanism by Richard Sennett engages sharply in this problematic, which becomes more present in relation to the expansion of the globalizing processes. However, the noticeable multiplication of resistances represents a new challenge for the cosmopolitan project.